Molecular bases of epigenetic mechanisms - Ezequiel Lacunza (Revista de la Sociedad Argentina de Diabetes, 2021)
The most common definition of epigenetics is derived from its own term: "epi" (above, above, beyond) and "genetic" (DNA sequence), referring to a layer of information that exists beyond that encoded in the DNA sequence, thereby making the genome work distinctively in different types of cells.